Kepemimpinan Kyai Dalam Pengasuhan Pesantren - Mukhroji Mukhroji (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: Islamic boarding schools as an educational institution with a total distinctive personality, always gives the freedom to determine the dynamic pattern of education policy. Kyai’s (Islam cleric) leadership who dared to hold an educational innovation makes the boarding schools as a barometer of Islamic education in Indonesia. Good leadership is both acceptable to all parties and able to lead under God’s guidance and to emulate the leadership of Prophet Muhammad based on akhlakul karimah (good attitude) and good habit (commendable) as siddiq, amanah, tabligh and fathonah. Keyword: Leadership, clerics, schools, and innovation.